1996
DOI: 10.1183/09031936.96.09040747
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deaminase (ADA) isoenzyme analysis in pleural effusions: diagnostic role, and relevance to the origin of increased ADA in tuberculous pleurisy

Abstract: The rise in adenosine deaminase (ADA) activity in the pleural fluid of tuberculous pleurisy patients, though used for diagnosis, is of unknown origin. In this work, we determined ADA activity and the activities of 2'-deoxyadenosine deaminase and ADA-2 in 350 patients. We also considered whether the results throw light on the origin of high pleural fluid ADA in tuberculous pleurisy and estimated the diagnostic efficiency of 2'-deoxyadenosine deaminase, ADA-2 and total ADA activities with and without the inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 18 publications
10
102
0
3
Order By: Relevance
“…They consisted mainly of malignancies, parapneumonias and congestive cardiac failure. Most of the malignancies were due to bronchial cancer, which is in agreement with Zemlin et al [10] Valdés et al [17] found that parapneumonic effusions were the most frequent reason for a high FADA, followed by carcinomas (with pleural metastatic lesions) and lymphomas.…”
Section: Discussionsupporting
confidence: 79%
“…They consisted mainly of malignancies, parapneumonias and congestive cardiac failure. Most of the malignancies were due to bronchial cancer, which is in agreement with Zemlin et al [10] Valdés et al [17] found that parapneumonic effusions were the most frequent reason for a high FADA, followed by carcinomas (with pleural metastatic lesions) and lymphomas.…”
Section: Discussionsupporting
confidence: 79%
“…23 Recently, it has been suggested that the test performance of ADA isoenzymes is superior to ADA, yielding lower false negative and false positive ¢ndings. 40,48,50 Finally, limitations of our study should be noted. First, misclassi¢cation bias can occur.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding patients with an early diagnosis of nontuberculous disease, notably malignancy and nontuberculous infection, may also help improve the utility of pfADA for TBPE. 5,9,[23][24][25][26] Diagnostic test accuracy depends on sensitivity and specificity, which are relatively stable, and pre-test probability that can be enhanced by selecting appropriate patients. In this study, we aimed to optimise its utility by increasing the pretest probability, and establish a local diagnostic pfADA cut-off value for adult TBPE.…”
Section: Introductionmentioning
confidence: 99%